Effectiveness of Lean Management to Reduce Waiting Time for Medicines at Hospital Outpatient Pharmacy (Universitas Muhammadiyah Yogyakarta, 2025)
Prolonged prescription waiting times continue to be a persistent challenge in many Indonesian hospitals, where studies on Lean management applications are still limited. The Indonesia Ministry of Health mandates a maximum 30-minute standard, yet compliance is often unmet, risking patient satisfaction and safety. This study employed a two-cycle action research approach using Value Stream Mapping (VSM) to analyze workflows and design targeted interventions in the outpatient pharmacy of a public hospital in Central Java. Across the two cycles—diagnosing, planning, action, and evaluation—both qualitative and quantitative assessments were conducted. The pharmacy processed an average of 150 prescriptions daily, with drug production identified as the main bottleneck, accounting for 61% of lead time. Lean interventions reduced non-value-added activities from eight to four, resulting in a 14.3% decrease in lead time (from 51.09 to 43.77 minutes) and an increase in the value-added ratio from 29.3% to 45.6%. Although the national target of ≤30 minutes was not achieved, the intervention demonstrated Lean’s potential to improve efficiency and foster staff awareness of waste reduction. This study presents a practical Lean model for hospitals in resource-limited settings, emphasizing the importance of sustained leadership and digital integration to achieve long-term improvement.